Uji Performansi pada Mesin Pengurai Sabut Kelapa dengan Modifikasi Pisau Pengurai - Suhendra Suhendra; Winda Apriani; Irma Fahrizal (Proklamasi 45 University, 2022)
Coconut coir can be processed into cocopeat and coco fiber. In the chopping process, the chopping mechanism has a critical role that will determine the results of the chopping off of coconut coir. Based on these conditions, in this study, the development of a chopping mechanism was carried out by modifying the chopper blade to improve the chopper of coconut coir. The purpose of this study was to modify the coconut coir chopper blade, perform performance tests and calculate the increased performance after modification. Modification of the chopper mechanism on the coconut coir chopper machine is done by replacing the type of chopper blade with an iron rod with a diameter of 4 mm which is sharpened at the end. The test data includes data on the capacity of coconut coir chopping, the percentage of cocopeat, the percentage of coco fiber, the percentage of unprocessed coconut coir, the percentage of material loss, and the increase in performance after modification. The modified coconut coir chopper mechanism has specifications of 240 mm long, 100 mm diameter, 39 blades, and ± 14 mm high. The test was carried out at a rotary speed of the chopper mechanism of 720 rpm. Based on the test result, the capacity of chopping coconut coir using a modified coconut coir chopper machine is 7,93 kg/hour, producing 45,57% cocopeat, 36,15% coco fiber, 13,15% coconut coir unprocessed and the loss reached 5,13%. Modifications on the chopper blade are proven to increase the performance of the coconut coir chopper machine by 297%.